Enhancing Islamic Education Teachers’ Quality Through Merdeka Mengajar Platform at SDN 01 Pragaan Laok - Annas Yulio Andrila; Ahmadi, Ahmadi (Penerbit Hellow Pustaka, 2026)
This study explores how the Merdeka Mengajar Platform (PMM) contributes to improving the teaching quality of Islamic Religious Education (IRE) teachers and identifies key barriers that hinder its optimal use at SDN 01 Pragaan Laok, Sumenep. Using a qualitative case study design, data were collected through structured classroom and platform-use observations (September–December 2024), in-depth interviews with the principal and IRE teachers, and documentation review. Data were analyzed using Miles and Huberman’s interactive model (data reduction, data display, and conclusion drawing/verification) supported by triangulation. The findings show that PMM strengthens teachers’ annual teaching performance planning, supports more systematic monitoring and evaluation of learning outcomes, and provides accessible professional development resources (microlearning, curated teaching materials, and peer-sharing). However, implementation is constrained by limited internet access and technology infrastructure, uneven digital skills, insufficient sustained training, time constraints, workload pressures, and occasional technical/administrative frictions in certain PMM features. The study recommends strengthening school-level mentoring, improving connectivity and device access, and designing continuous, context-sensitive professional development for IRE teachers so PMM can more consistently translate into improved classroom practices and student learning experiences.